2020
DOI: 10.3390/biom10081173
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification and Characterization of New microRNAs in Human Platelets Stored in a Blood Bank

Abstract: Platelet concentrate (PC) transfusions are widely used to save the lives of patients who experience acute blood loss. MicroRNAs (miRNAs) comprise a class of molecules with a biological role which is relevant to the understanding of storage lesions in blood banks. We used a new approach to identify miRNAs in normal human platelet sRNA-Seq data from the GSE61856 repository. We identified a comprehensive miRNA expression profile, where we detected 20 of these transcripts potentially expressed in PCs stored for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…As platelets suffer storage damage or are activated by the presence of microorganisms, there is an initial process of the degradation of miRNAs that reduces their quantity. However, this process ceases, and some miRNAs may have their quantity increased as the cell damage or sepsis progresses, as RNA-editing enzymes such as RNase and RNA helicases increase the quantity of certain miRNAs by cleaving miRNA precursors (pre-miRNAs) into mature miRNAs in response to oxidative stress [ 8 , 10 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As platelets suffer storage damage or are activated by the presence of microorganisms, there is an initial process of the degradation of miRNAs that reduces their quantity. However, this process ceases, and some miRNAs may have their quantity increased as the cell damage or sepsis progresses, as RNA-editing enzymes such as RNase and RNA helicases increase the quantity of certain miRNAs by cleaving miRNA precursors (pre-miRNAs) into mature miRNAs in response to oxidative stress [ 8 , 10 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…When platelets are not activated (that is, when they are in a physiologically normal stage), the quantity of miR-127 is greater than that of miR-320a. When the platelet concentrate (PC) stored in a blood bank undergoes aging due to excessive storage time or contamination by microbial agents, the degradation of miR-320a is lower than that of miR-127, and as a result miR-320a is present at a higher concentration [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation is the updating of precursor and mature microRNA sequence databases. A recent study, 60 based on the latest version of miRbase, comprehensively summarizes the diverse repertoire of miRNAs that are identified in platelets stored in blood banks for 6 days. These findings are further validated using quantitative real‐time polymerase chain reaction (qPCR).…”
Section: Psls At 20–24°c Under Constant Horizontal Agitationmentioning
confidence: 99%
“…Therefore, it is essential to screen molecular biomarkers to assess and monitor the physiological viability of platelets in PC. Maués et al [ 4 ] used an approach to identify miRNAs in normal human platelet sRNA-Seq data from the GSE61856 repository. A new collection of miRNAs (miR-486-5p, miR-92a-3p, miR-103a-3p, miR-151a-3p, miR-181a-5p, and miR-221-3p) was identified by their study that showed a sensitivity expression pattern due to biological platelet changes during storage.…”
mentioning
confidence: 99%